Molecular Cell Biology - Harvey F Lodish [ et.al... ] (W.H.Freeman & Co Ltd, 2016)
This is the textbook only without LaunchPad.With its acclaimed author team, cutting-edge content, emphasis on medical relevance, and coverage based on key experiments, Molecular Cell Biology has justly earned an impeccable reputation as an exciting and authoritative text. Avoiding an encyclopaedic approach, the book grounds its coverage in the experiments that define our understanding of cell biology, engaging students with the exciting breakthroughs that define the field's history and point to its future. The authors, all world-class researchers and teachers, incorporate medically relevant examples where appropriate to help illustrate the connections between cell biology and health and human disease.Molecular Cell Biology can also be purchased with W.H. Freeman's breakthrough online course space, LaunchPad, which offers innovative media content, curated and organised for easy assignability. Including LearningCurve, our adaptive quizzing resource, to engage your students and develop their understanding of molecular cell biology. To order this book bundled with